THE INFLUENCE OF E-SERVICE QUALITY AND PERCEIVED VALUE WITH E-TRUST AS A MEDIATION VARIABLE ON CUSTOMER SATISFACTION OF P2P LENDING APPLICATIONS IN EAST JAVA - Setiabudi, Ricky Austin; Sutanto, J.E. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to examine the influence of e-service quality and perceived value with e-trust as a mediating variable on Customer Satisfaction in P2P lending applications in East Java. This study employs a quantitative approach, and non-probability sampling is used to gather data from 160 respondents who are Customers of P2P lending applications in East Java. The validation and reliability of the research instrument are tested using SPSS with a sample of 30 P2P lending application Customers in Surabaya. Data processing involves partial least square (PLS) with testing of the measurement model (outer model) and the structural model (inner model). The results indicate that e-service quality has a positive and significant influence on Customer Satisfaction in P2P lending applications, perceived value has a positive and significant impact on Customer Satisfaction in P2P lending applications, e-trust positively and significantly influences Customer Satisfaction in P2P lending applications, e-service quality has a positive and significant impact on e-trust, perceived value has a positive and significant impact on e-trust, and e-trust novelty mediates e-service quality and perceived value on Customer Satisfaction in P2P lending applications